Pendampingan Guru Madrasah Diniah dalam Meningkatkan Kualitas Keagamaan Siswa di SMA Nurul Jadid - Muhammad Ainul Yaqin; Ahmad Mufrih Naufal Mamduh; Husni Anwar (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Nurul Jadid Senior High School (SMA NJ) is one of the schools under the auspices of the Nurul Jadid Paiton Probolinggo Islamic Boarding School. This institution not only emphasizes formal lessons but also emphasizes religious lessons which are highly emphasized to the point of growing madrasah diniyah in the institution. In the current era, new breakthroughs are needed so that Madin can survive in the increasingly tight competition in the education services business. The institution's steps in making changes must of course be adjusted to the condition of its human resources. That's why at Madin educational institutions it is carried out every 2 days a week. In an effort to increase Madrasah Diniyah activities in schools, several methods have been implemented so that the activities at Madrasah Diniah which are carried out at Nurul Jadid High School often change and the implementation of the current activity method is by dividing the days with formal schools which were originally one week for full school. So Seka has now been changed to four days of formal school and two days of Madrasah Dinah school. Nurul Jadid High School provides various educational support facilities for students. There are many teachers who are competent in their fields, learning support activities such as Madrsah Diniyah, extracurriculars, student organizations, learning communities, sports teams and libraries, but at NJ High School, apart from studying formal science, NJ High School is very There is also emphasis on religious education carried out by Madin (Madrasah Diniyah) which is carried out 2 days a week so that the institution also increases students whose religion is broad and can be applied in daily activities.